2015
DOI: 10.1371/journal.pone.0144872
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Associated with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: BackgroundPrior work suggested that patients with inflammatory bowel diseases (IBD) have lower body mass index (BMI) than controls and patients with lower BMI have more serious complications.GoalThe study was aimed to find relationship between BMI in patients with and without IBD, investigate effects of medicine therapy and disease stages on patients’ BMI.MethodsPotentially eligible studies were identified through searching PubMed, Cochrane and Embase databases. Outcome measurements of mean BMI and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 52 publications
(68 reference statements)
7
43
0
1
Order By: Relevance
“…Although this contradicts the results of Ng and colleagues who reported an inverse association between childhood BMI and UC. The results of the current study are consistent with reports from prospective and retrospective studiesand systematic reviews . Jensen et al suggested that the association could reflect the consequences of altered immunology or gut microbiota induced by being underweight during childhood an argument supported by Abraham and colleagues .…”
Section: Discussionsupporting
confidence: 91%
“…Although this contradicts the results of Ng and colleagues who reported an inverse association between childhood BMI and UC. The results of the current study are consistent with reports from prospective and retrospective studiesand systematic reviews . Jensen et al suggested that the association could reflect the consequences of altered immunology or gut microbiota induced by being underweight during childhood an argument supported by Abraham and colleagues .…”
Section: Discussionsupporting
confidence: 91%
“…The association between SFH and low BMI is in line with other studies on persons who avoid gluten or have Crohn’s disease [2123]. Previous studies have also suggested an increased risk of inadequate nutrition in subgroups of SFH [37, 38], and the nutritional state among persons with SFH seems to be worth further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…A study on food allergy, one of the subgroups of SFH, suggested that it is more often reported among city residents [20]. Studies on other subgroups of SFH, such as individuals with Crohn’s disease and gluten sensitive persons, indicated that they have a lower body mass index (BMI) than controls [2123]. Other studies on celiac disease and irritable bowel syndrome showed that these diseases led to an increased burden on the subject’s partner [24, 25], which may contribute to a lower degree of couple relationships among people with SFH.…”
Section: Introductionmentioning
confidence: 99%
“…72 These findings were not reproduced in a European cohort, which showed no association between obesity and IBD in adults, 73 and a meta-analysis of 24 studies that included 1442 adult patients with IBD disease and 2059 healthy controls showed that obesity was less prevalent in patients with Crohn’s disease (OR, −1.88; 95% CI, −2.77 to −1.00) and that there was no difference in ulcerative colitis. 74 On the other hand, in children, the prevalence of obesity in IBD was similar to that in the general population, but obese children with IBD had more severe disease than normal-weight children. 75 The latter study also identified that treatment with corticosteroids may be a confounder in the interpretation of the relationship between obesity and IBD because the steroid treatment may have predisposed to the development of obesity.…”
Section: Small Intestinementioning
confidence: 86%